Building Business Networking: A Proposed Framework for Malaysian SMEs - Farinda, A.G.; Kamarulzaman, Y.; Abdullah, A.; Ahmad, S.Z. (Zia World Press, Australia, Australia, 2009)
Social network is a significant value-added to business environments especially to the Small and Medium-sized Enterprises (SMEs). It is built when businesses interact with each other in the community, by exchanging rich and thoughtful experiences among themselves through various means. Little research has focused on how the business networking is valued in enhancing SMEs’ business performance in Malaysia. The goal of this paper is to examine the importance of business networking as a critical success factor to SMEs in Malaysia. It describes how business network could be created based on six motives, adapted from Oliver, 1990, into why organisations are involved in business networks. Amongst the motives are necessity, asymmetry, reciprocity, efficiency, stability and legitimacy. The paper then present the proposed framework of business networking based on previous literature. The findings in this paper shall be useful for SMEs that are seeking for ways to develop and to attain success in their business.